EVALUASI KESESUAIAN LAHAN TANAMAN CENGKEH (Eugenia aromatic L.) DI SUB DAERAH ALIRAN SUNGAI NOONGAN - J., M., Mawara (AgriPeat, 2020)
Watershed is an area that has strategic potential in the form of natural resources, land, vegetation and water in it has a sources of human resources which can be grown and developed as a source of incame and prosperity for the region and nationally. Upstream of the watershed, a very important zona that needs to be considered in efforts to This study aims to determine the land suitability (actual, potential and economic) of clove plant(Eugenia aromatic L.) in the Noongan sub-watershed. The method used was a survey with the land unit ((LU) approach and data analysis was carried out using the ALES (Automated Land Evaluation System) program. The results showed that the suitability of clove plant in the Noongan sub-watershed was the land suitability of the actual, very suitable (S1) in LU (land unit)1, marginal suitable (S3) (S3rc, S3oa/rc, S3rc/eh, S3kl/kb, S3rc/kl/eh/kb, S3rc/kl/eh/ktk/kb in Land unit(LU) 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 and 14 with limiting factors in the availability of oxygen (oa) drainage, rooting media (rc) texture and erosion hazard (eh), slopes, ktk and kb. Assessment of potential land suitability is S1, S2rc, S2kl, S2rc/oa, S2rc/kl, S2rc/eh, S2rc/kl/eh. Net present value (NPV) economic feasibility assessment is obtained NPV value of 54,981,666.67 (S1) Land unit (LU) 1; NPV value of 42,981,666.67 (S2) Land unit (LU) 2,4,10,13 and NPV value of 10,091,666.67 (S3) Land unit (LU) 3,5,6,7,8,11,12 and 14. And internal rate of return (IRR) shows IRR value of 38,40 % (S1) Land unit (LU) 1; IRR value of 34,78 % (S2) Land unit (LU) 2,4,10 and IRR value of 30,26 % Land unit (LU) 3,5,6,7,8,9,11,12,13 and 14. NPV and IRR values show positive values so that the clove plant are feasible to be cultivated on an ongoing basis